CHANGING INSTITUTIONAL DESIGN OF THE FINANCIAL SERVICES MARKET IN UKRAINE IN THE CONTEXT OF POST-CRISIS RECOVERY - Hlushchenko, Olha (Social Economics, 2020)
The article determines the changes having taken place in institutional design and identifies trends in the recovery of the financial services market as a complex systemic phenomenon. The essence of current tendencies on the market of financial services of Ukraine as well of those in the period of crisis is revealed. Their influence on the financial system of our country is also determined. The research conducted showed that the vast majority of subjects of the Ukrainian financial services market have experienced a significant decrease.This is especially true of banks and credit unions, though the number of financial companies is growing. The growth in the number and amount of the activities of financial companies suggests that the microcredit sector is also growing. Slowing down real salary increases indicates a loss of public confidence in banks and in the future may lead to a decline in effective demand of the population. This has led to the conclusion that the credit market of Ukraine is becoming non-institutionalized. These processes have led to a concentration of capital in the credit segment of the financial services market. The decline in the number of financial institutions is not critical to the market while the growing number of non-bank financial intermediaries is considered to be a negative trend.The deep socio-political crisis has caused capital outflows from the Ukrainian stock market and the reduction in the volume of contracts at the domestic stock exchanges. This is clearly a negative trend, since the decrease in the volume of contracts on the stock market is one of the factors that affect the investment climate and reflect investors’ interest in buying securities of domestic companies. State regulation of the financial services market needs to be reformed in two stages: the first is to reduce the number of regulators to two and move to a task-based patter with the division into licensing activities and macro-prudential supervision; the second is the transition to a single regulator. This is in line with current global trends and will make government regulation of the financial services market comprehensive and systematic in order to avoiding hyper-regulation and lack of regulatory influence in certain market segments